A Squaraine‐Linked Mesoporous Covalent Organic Framework1. Issue 13 (21st February 2013) - Nagai, Atsushi; Chen, Xiong; Feng, Xiao; Ding, Xuesong; Guo, Zhaoqi; Jiang, Donglin
<x xml:space="preserve">Abstract</x> π in the sky: A squaraine‐linked, conjugated two‐dimensional porphyrin covalent organic framework (COF; see scheme; C: gray, H: white, N: blue, Cu: red) was synthesized. Owing to the π‐conjugated linkage together with the eclipsed stacking of the units, this COF exhibits enhanced chemical and thermal stabilities. It absorbs a broad range of light, from the ultraviolet to the visible, and near‐infrared regions, and shows potential as a photocatalyst.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>